Protein families : relating protein sequence, structure, and function - Orengo, Christine A., 1955-; Bateman, Alex, 1972-; Wiley eBooks (Hoboken, New Jersey : John Wiley & Sons, 2014)
"This book describes approaches for recognizing and classifying proteins into families of evolutionary related proteins. Reviewing all the major resources for classifying protein families, the book combines descriptions of general philosophies of protein family classification systems with detailed descriptions and examples of selected families found in different biological systems. Scientists in diverse areas of biology and protein science will learn how to use the various resources and databases and gain valuable insight into how proteins evolve and how new functional repertoires emerge"--
Includes index.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Proteins; Proteomics; Molecular biology -- Data processing; Bioinformatics; Proteins; Proteomics; Computational Biology; COMPUTERS -- Bioinformatics; Bioinformatics; Molecular biology -- Data processing; Proteins; Proteomics; Electronic books